2020
DOI: 10.3390/polym12102398
|View full text |Cite
|
Sign up to set email alerts
|

Desiccation Cracking Behavior of Polyurethane and Polyacrylamide Admixed Clayey Soils

Abstract: There has been a growing interest in polymer applied for soil reinforcement in recent years. However, there little attention has been paid to the effects of polymer on soil cracking behavior, and cracks significantly change soil strength and hydraulic properties and alter reinforcement effectiveness. This study investigated the desiccation cracking behavior of polyurethane (PU) and polyacrylamide (PAM) admixed clayey soils with different polymer concentrations by performing desiccation cracking tests. Scanning… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 52 publications
0
8
0
Order By: Relevance
“…Aggregate stability and hydraulic conductivity data shown here might be explained by the reinforcement mechanism of Ca-bacterial alginate hydrogel exerted among the soil particles. The mechanism is based on the strong adhesion of the biopolymer with the soil particles [ 9 , 56 , 57 ]. The physical structure of this reinforcement can be seen under bright field microscopy ( Figure 6 ).…”
Section: Discussionmentioning
confidence: 99%
“…Aggregate stability and hydraulic conductivity data shown here might be explained by the reinforcement mechanism of Ca-bacterial alginate hydrogel exerted among the soil particles. The mechanism is based on the strong adhesion of the biopolymer with the soil particles [ 9 , 56 , 57 ]. The physical structure of this reinforcement can be seen under bright field microscopy ( Figure 6 ).…”
Section: Discussionmentioning
confidence: 99%
“…Doyle [26] studied the erosion behavior of polyurethane under insulation conditions and found that local deformation and high strain led to the temperature increase of the erosion zone, and the mechanical and thermal stresses led to the degradation and loss of the polyurethane. Barkoula, Qi, and Hao et al [17,[27][28][29] believe that there are three main ways in which solid particles impact polyurethane, namely elastic impact, plastic impact, and elasticplastic impact. Because the polyurethane material has a certain elasticity, pure plastic impact rarely occurs in polyurethane materials.…”
Section: Introductionmentioning
confidence: 99%
“…However, research in this aspect has been limited so far. In a series of laboratory desiccation cracking tests on a clayey soil, Qi et al (2020) assessed the effect of polyurethane (PU) and polyacrylamide (PAM) admixtures. Different concentrations between 0.25 and 1 wt% for PU and between 0.025 and 0.1 wt% for PAM were tested.…”
Section: Introductionmentioning
confidence: 99%